CIVILIAN AIRCRAFT TRANSPONDER MANIPULATION IN RECONNAISSANCE MISSIONS, AERIAL INCIDENTS CASES AND CHICAGO CONVENTION 1944 - Pratama, Garry Gumelar; Nanda, Muhammad Rifqi Putra (Faculty of Law Universitas Padjadjaran, 2023)
Throughout 2020, the People's Republic of China (PRC) stated that the United States (US) manipulated the electronic identity code of its military aircraft (transponder code) over the South China Sea by using the identity of a civilian aircraft to carry out reconnaissance missions. The discussion of the incidents has faded in the past two years, even being regarded by some observers as a 'common' practice having been used since the Cold War era by the US. These incidents have never been heard to reappear in the South China Sea situation. However, the escalation of reconnaissance practices heated up again after a PRC's high altitude balloon was shot down by a US fighter jet over the US's territorial sea on February 4, 2023. The US had claimed that the aircraft was on a spy mission. This incident could be a starting point for the US to resume the practices throughout 2020 by imprisoning civilian aircraft in the South China Sea or even on the PRC's mainland because this practice is considered 'common' on the US side. By using the international legal research method, in which international legal sources are juxtaposed with the current context in the field, this article concludes that the practice of manipulating civil transponder codes cannot be justified as a 'common' practice because it is endangered the civil aviation and contrary to the Chicago Convention 1944.